2008
DOI: 10.4049/jimmunol.181.9.6467
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Hepatitis B Virus Replication Is Not Affected by Protein ISG15 Modification but Is Reduced by Inhibition of UBP43 (USP18) Expression

Abstract: Hepatitis B virus (HBV) causes both acute and chronic infection of the human liver and is associated with the development of liver cirrhosis and hepatocellular carcinoma. UBP43 (USP18) is known as an ISG15-deconjugating enzyme and an inhibitor of type I IFN signaling independent of its enzyme activity. In this study, we examined the role of these two previously identified functions of UBP43 in the innate immune response to HBV viral infection. As an in vivo HBV replication model system, a replication-competent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 45 publications
(51 reference statements)
1
58
0
Order By: Relevance
“…For example, ISG15 can have an antiviral effect on Sindbis virus, influenza virus, HSV, human immunodeficiency virus (HIV) and Ebola virus (Lenschow et al, 2005(Lenschow et al, , 2007Okumura et al, 2006;Zhang et al, 2007), but ISGylation does not contribute to murine susceptibility to lymphocytic choriomeningitis virus and vesicular stomatitis virus , nor to hepatitis B virus replication in ISGylation-deficient mice (Ube1L 2/2 ) (Kim et al, 2008a). Although ISG15 may also promote viral production by acting as a negative regulator of the innate immune response through its conjugation to RIG-I (Kim et al, 2008b), this mechanism is unlikely to contribute to our observed effects, as Huh7.5 cells are deficient in RIG-I (Sumpter et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ISG15 can have an antiviral effect on Sindbis virus, influenza virus, HSV, human immunodeficiency virus (HIV) and Ebola virus (Lenschow et al, 2005(Lenschow et al, , 2007Okumura et al, 2006;Zhang et al, 2007), but ISGylation does not contribute to murine susceptibility to lymphocytic choriomeningitis virus and vesicular stomatitis virus , nor to hepatitis B virus replication in ISGylation-deficient mice (Ube1L 2/2 ) (Kim et al, 2008a). Although ISG15 may also promote viral production by acting as a negative regulator of the innate immune response through its conjugation to RIG-I (Kim et al, 2008b), this mechanism is unlikely to contribute to our observed effects, as Huh7.5 cells are deficient in RIG-I (Sumpter et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…ISG15 2/2 mice are more susceptible to influenza A and B viruses, herpes simplex virus type 1 (HSV-1), Sindbis virus and murine gammaherpesvirus 68 infection; for Sindbis virus, this effect is dependent on ISGylation (Lenschow et al, 2007). Whilst these studies suggest a general role for ISG15 as an antiviral agent, a recent report found that ISG15 can inhibit IFN responses after infection by Newcastle disease virus (Kim et al, 2008a). ISGylation of the antiviral RIG-I enzyme inhibited IFN signalling in MEF cells (Kim et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…UBP43-deficient mice show a severe phenotype characterized by brain cell injury, poly(I-C) hypersensitivity, and premature death (36,46). Interestingly, they are resistant to otherwise fatal cerebral infections with lymphocytic choriomeningitis virus and vesicular stomatitis virus (45) and have substantially lower hepatitis B virus DNA levels in a mouse model of acute hepatitis B (22). Importantly, USP18/UBP43 is elevated in livers of future nonresponders to pegIFN-␣ therapy (5,47).…”
mentioning
confidence: 99%
“…For example, it has been shown that a reduced level of expression of USP18/UBP43 results in increased AV activity against Sindbis virus, hepatitis B (HepB) virus, and vesicular stomatitis virus (VSV) in knockout mice (17,20,24,25,31). USP18/ UBP43 can also negatively regulate IFN signaling by binding to IFNAR2 and downregulating the JAK-STAT pathway (24); this property is distinct from its ISG15 deconjugation activity described above.…”
mentioning
confidence: 99%